Three Week or One Week Bladder Catheterization in Reducing Urethrocutaneous Fistula for Hypospadias Repair: A Randomized Controlled Trial - Shrestha, Sandesh; Shrestha, Gyaneswhor; Verma, Rupesh; Koirala, Dinesh P; Chapagain, Suman; Dahal, Geha R (Journal of Institute of Medicine Nepal, 2021)
Introduction: Surgical correction is the only treatment for hypospadias. Complication rate is usually high. Indwelling catheter is kept postoperatively for urinary diversion and proper healing. There is no consensus regarding the duration of catheterization. This study was conducted to compare urethrocutaneous fistula (UCF) rate between one and three weeks of catheterization. Methods: This study was a randomized control trial, conducted at Tribhuvan University Teaching Hospital, Kathmandu, Nepal. All children undergoing urethroplasty for hypospadias were randomized into two groups. After surgery, urinary catheter was kept for one and three weeks in group 1 and group 2 respectively. Occurrence of UCF and other complications were noted and compared between the groups. Results: A total of 32 patients were randomized in to 2 groups having 16 in each group. Fourteen (43.8%) developed UCF. In one week group, 8 (50%) and in three week group 6(37.5%) developed UCF. It was not statistical different (p = 0.48). Occurrence of UCF was not different in different age of children, type of hypospadias and single or staged procedure. Meatal stenosis was not different in both groups. Conclusion: Incidence of UCF was not different in one week or three week of urinary catheterization after surgery for hypospadias.